Master Candidates Usage of Reading Comprehension Strategies in Academic Context - Murad Zangana, Ibtihal (Opción, 2019)
Success at academic context depends on the students’ ability to understand an English written text. The subjects of the current study are 13 postgraduate college students who wish to apply for master degree studies. Reading com- prehension was the most problematic issue at their path. The current study investigates the impact of using reading comprehension strategies (RCS) on maximizing the students’ ability to process a written academic text. The stu- dents enrolled in a three week coaching session of English language reading comprehension. The session focused on the “how” and “when” use of (RCS). Six RCS were under observation, namely: Predicting, Visualizing, Summariz- ing, Inferring, Scanning, and Identifying Main Idea. The results of this action research revealed that implementing RCS in curriculum led to significance development in academic context. The results also showed the students were selective in their usage of RCS.